English as Academic Lingua Franca in Latin American Doctoral Education? - Ávila Reyes, Natalia (International Higher Education, 2022)
While English requirements in higher education have increased worldwide, the language of instruction in Latin America tends to be Spanish or Portuguese. This article addresses the challenges that doctoral programs face when promoting both English as a means of academic participation and Spanish as a valid language for fostering regional scientific development.